Vitamin D deficiency in a European inflammatory bowel disease inception cohort: an Epi-IBD study. Issue 11 (November 2018) - Chetcuti Zammit, Stefania; Ellul, Pierre; Girardin, Giulia; Valpiani, Daniela; Nielsen, Kári R.; Olsen, Jóngerð; Goldis, Adrian; Lazar, Daniela; Shonová, Olga; Nováková, Marie; Sebastian, Shaji; Whitehead, Emma; et al.
Abstract : Background: Serum vitamin D level is commonly low in patients with inflammatory bowel disease (IBD). Although there is a growing body of evidence that links low vitamin D level to certain aspects of IBD such as disease activity and quality of life, data on its prevalence and how it varies across disease phenotype, smoking status and treatment groups are still missing. Materials and methods: Patients diagnosed with IBD between 2010 and 2011 were recruited. Demographic data and serum vitamin D levels were collected. Variance of vitamin D level was then assessed across different treatment groups, disease phenotype, disease activity and quality of life scores. Results: A total of 238 (55.9% male) patients were included. Overall, 79% of the patients had either insufficient or deficient levels of vitamin D at diagnosis. Patients needing corticosteroid treatment at 1 year had significantly lower vitamin D levels at diagnosis (median 36.0 nmol/l) ( P =0.035). Harvey–Bradshaw Index ( P =0.0001) and Simple Clinical Colitis Activity Index scores ( P =0.0001) were significantly lower in patients with higher vitamin D level. Serum vitamin D level correlated significantly with SIBQ score ( P =0.0001) and with multiple components of SF12. Smokers at diagnosis had the lowest vitamin D levels (vitamin D: 34 nmol/l; P =0.053). Conclusion: This study demonstrates the high prevalence of low vitamin D levels in treatment-naive European IBD populations. Furthermore, it demonstrates the presence of low vitamin D levels in patients with IBD who smoke.